NERACA AIR DAN POTENSI AIR TANAH DAERAH SEMARANG DAN SEKITARNYA PROPINSI JAWA TENGAH - PRATIKNYO, PUJI
Geographically, the study area lies on the coordinate between 110°10\'34\" East longitude - 110°30\' East longitude and 6°53\'34\" South latitude - 7°12\'10\" South latitude, with elevation ranges 0 in and 2050 m from mean sea level. The area is about 716,375 km2 square, including Kodya Semarang, northen part of Kabupaten Semarang, eastern part of Kabupaten Kendal, and western part of Kabupaten Demak. The main problem of the study is that some of groundwater wells which were previously artesian in the past, become to be =artesian in the present and we find some indications of the occurence of some subsidence at some locations in the north part of the study area. A water balance and groundwater potential computation are done by using both primary and secondary data wined with A basic theory and an interpretation, either deduc tionally and inductionally. This method is expected to be able to give an ilustration about the groundwater condition, and to solve the main problem. The result of this study shows that the elements of water balance have a relatively high value in January, February, March, April, November and December, and have a low value even nearly zero in May, June, July, August, September and October. A grmmdwater quality of the study area, generally, falls in the range of drinking water standart, and the groundwater flows from South to North. Rain water which supllies the groundwater as a groundwater reservoir = 561.30 mm/year = 19.87% of rain falls 298,592,763.75 m3/year. The study area can be deviled into 4 potential zones of recharge area, i.e: 1. Very good recharge area zone, about 39% of the study area 2. Good recharge area zone, about 36% of the study area 3. Fair recharge area zone, about 11% of the study area 4. Not good recharge area zone, about 14% of the study area.